Beef safety - current research and summary of progress - F. Cunningham; Melvin C. Hunt; Curtis L. Kastner; Donald H. Kropf; B. Larson; D. Schafer; D. Simms; S. Smith; M. Vanier; Daniel Y.C. Fung (Kansas Agricultural Experiment Station Research Reports, 1991)
Beef and beef products are significant parts of a balanced diet in the U.S. and major parts of the Kansas economy. Therefore, these products must be carefully processed, handled, and monitored for microbial quality to ensure safety for the consumer. KSU Animal Sciences research is designed to accomplish this end and to enhance demand for beef. We have made a major commitment to beef safety research. Moreover, results with beef are generally applicable to other meats.
Keywords: Cattlemen& #x27; s Day; 1991; Kansas Agricultural Experiment Station contribution; no. 91-355-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 623; Beef; Beef products; Microbes; Safety